Ammonium hexafluorosilicates as potential anti-caries agents: the problem of cation selection - V. O. Gelmboldt; I. V. Lytvynchuk (The State Expert Center of the Ministry of Health of Ukraine, 2021)
In the last decade, ammonium hexafluorosilicate (AHFS) and ammonium hexafluorosilicates with biologically active cations (AHBAC), which have certain advantages over traditional fluoride medicinal substances, have been actively studied as anti-caries agents. In particular, an important feature of the action of AHFS is its ability to cause prolonged occlusion of the dentinal tubules with a precipitate of calcium fluoride; when using AHBAС there is a possibility of strengthening the anti-caries activity of the substance due to the pharmacological potential of the cation. The purpose of the review is to analyze the effects of the cation on the physicochemical properties and biological activity of ammonium hexafluorosilicates as potential anti-caries agents. Research methods - bibliosemantic, content analysis. It was drew the attention to the peculiarity of the AHBAC structure: salt structures are formed on the basis of systems of strong interionic H-bonds, mainly of the NH···F type, which have a significant effect on the properties of hexafluorosilicates in the crystalline state and their behavior in solutions. It was demonstrated the non-trivial nature of the change of solubility in water of AHBAC with heterocyclic and aromatic cations, which consists in the decrease of solubility with increasing number of hydrophilic fragments in the structure of cations. Adequate 2D QSPR models for interpretation and virtual screening of AHBAC water solubility have been constructed. Accounting for the effect of H-bonds on the solubility of AHBAC was detailed. It was assumed that the process of hydrolysis of AHBAC in aqueous solutions can be stimulated by elongation of the Si-F anion bonds due to the effects of H-bonds. It is shown that the thermal stability of AHBAC with pyridinium cations symbatically correlates with the number of strong and medium H-bonds in salt structures. The action of the pharmacological effects of the cation on the biological activity of AHBAC is manifested in the form of an increase in the caries-prophylactic efficacy of AHBAC in comparison with a similar effect of AHFS. Attempts to establish a relationship between the anti-caries activity of AHBAC and a certain pharmacological action of the cation have led to mixed results. This obviously reflects the complex mechanism of the influence of the biological activity of the cation on the caries-prophylactic efficacy of hexafluorosilicates, which is not limited to any one, albeit dominant, type of activity.